Pharmacological Inhibition of the Ubiquitin Ligase RNF5 Rescues F508del-CFTR in Cystic Fibrosis Airway Epithelia. Issue 7 (19th July 2018) - Sondo, Elvira; Falchi, Federico; Caci, Emanuela; Ferrera, Loretta; Giacomini, Elisa; Pesce, Emanuela; Tomati, Valeria; Mandrup Bertozzi, Sine; Goldoni, Luca; Armirotti, Andrea; Ravazzolo, Roberto; Cavalli, Andrea; et al.
Summary: In cystic fibrosis (CF), deletion of phenylalanine 508 (F508del) in the CFTR channel is associated with misfolding and premature degradation of the mutant protein. Among the known proteins associated with F508del-CFTR processing, the ubiquitin ligase RNF5/RMA1 is particularly interesting. We previously demonstrated that genetic suppression of RNF5 in vivo leads to an attenuation of intestinal pathological phenotypes in CF mice, validating the relevance of RNF5 as a drug target for CF. Here, we used a computational approach, based on ligand docking and virtual screening, to discover inh-02, a drug-like small molecule that inhibits RNF5. In in vitro experiments, treatment with inh-02 modulated ATG4B and paxillin, both known RNF5 targets. In immortalized and primary bronchial epithelial cells derived from CF patients homozygous for the F508del mutation, long-term incubation with inh-02 caused significant F508del-CFTR rescue. This work validates RNF5 as a drug target for CF, providing evidence to support its druggability. Graphical Abstract: Highlights: Homology modeling/virtual ligand screening identified RNF5 inhibitor inh-2 Inh-2 rescues F508del-CFTR activity on human primary bronchial epithelia Inh-2 decreases ubiquitylation and increases half-life of F508del-CFTR Inh-2 modulates RNF5 downstream pathways Abstract : Sondo et al. used a computational approach to identify an inhibitor, named inh-02, for RNF5 ubiquitin ligase. RNF5 detects the misfolding of a mutant CFTR in cystic fibrosis. Inh-2 decreases ubiquitylation and rescues F508del-CFTR on human primary bronchial epithelia. This work validates RNF5 as a drug target for cystic fibrosis.